Root distribution, partitioning of dry matter and nutrient uptake in ‘Thompson Seedless’ grapes (Vitis vinifera) grafted on different rootstocks - SOMKUWAR, R G; SATISHA, J; RAMTEKE, S D; SHARMA, J (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004-05 on the root distribution pattern of 4 grape rootstocks, namely ‘Dog Ridge’, ‘Salt Creek’, ‘1613- C’ and ‘St. George’ grafted Thompson Seedless (Vitis vinifera L.). The soil is heavy black cotton soil (vertisols) with pH of > 8.0. Roots of different thickness, viz < 2 mm, 2–5 mm, 5–10 mm, and >10 mm, were examined at a depth of 0–30, 31–60 and 61 – 90 cm from the surface. Dog Ridge putforth maximum root length in < 2 mm category at 0–30 cm distance from the trunk, while at 30–60 cm distance, ‘Salt Creek’ recorded maximum root length in < 2 mm category. The total root length of 2–5 mm category was higher at 31–60 cm distance both in ‘Dog Ridge’ and ‘St. George’. The total root length of 5–10 mm category was highest in ‘Dog Ridge’, followed by ‘Salt Creek’ and ‘St. George’. The spread of thicker roots of >10 mm till 60 cm distance, beyond which there was no spread in all the rootstocks. At 0–30 cm depth, ‘Dog Ridge’ put forth greater root mass, followed by ‘Salt Creek’ and ‘St. George’. But, highest root mass was recorded in all the rootstocks at 30–60 cm depth. The food material (dry matter) is stored in different parts of grapevine after back pruning. Considering the major vine part, ie trunk, the dry matter accumulation was highest in ‘Thompson Seedless’ grafted on ‘Dog Ridge’ (69.48%), while ‘St. George’ was last in the order (43.79%). Canes of ‘Salt Creek’ grafted vines produced highest dry matter (73.57%) while primary arms and trunk on ‘Dog Ridge’ grafted vines recorded highest dry matter of 72.64 and 69.48% respectively. However less dry matter was recorded in roots of ‘1613-C’grafted vines. The nitrogen accumulation in trunk of ‘Salt Creek’ rootstock was higher (1.45%). Similarly, the phosphorous was accumulated more (0.25%) in canes of ‘St. George’. Potash was accumulated more in canes as compared to other parts in ‘St. George’ and it was moderate in ‘Dog Ridge’ rootstock. Considering the parameters studied in the present investigation, among the rootstock, ‘Thompson Seedless’ grafted on ‘Dog Ridge’ rootstock seems to be better as compared to other rootstocks.